Notch and Hedgehog Signaling Unveiled: Crosstalk, Roles, and Breakthroughs in Cancer Stem Cell Research - Sabina Iluta; Madalina Nistor; Sanda Buruiana; Delia Dima (Life)
The development of therapies that target cancer stem cells (CSCs) and bulk tumors is both crucial and urgent. Several signaling pathways, like Notch and Hedgehog (Hh), have been strongly associated with CSC stemness maintenance and metastasis. However, the extensive crosstalk present between these two signaling networks complicates the development of long-term therapies that also minimize adverse effects on healthy tissues and are not overcome by therapy resistance from CSCs. The present work aims to overview the roles of Notch and Hh in cancer outburst and the intersection of the two pathways with one another, as well as with other networks, such as Wnt/β-catenin, TGF, and JAK/STAT3, and to explore the shaping of the tumor microenvironment (TME) with specific influence on CSC development and maintenance.